2017
DOI: 10.3390/su9060891
|View full text |Cite
|
Sign up to set email alerts
|

Public Participatory Mapping of Cultural Ecosystem Services: Citizen Perception and Park Management in the Parco Nord of Milan (Italy)

Abstract: Ecosystem services may be underestimated, and consequently threatened, when land-use planning and management decisions are based on inadequate information. Unfortunately, most of the studies aimed to evaluate and map cultural ecosystem services (CES) are not used for actual decision support therefore there is a gap in the literature about its use in practice. This study aimed to reduce this gap by: (i) mapping CES perceived by city park users through participatory mapping (PPGIS); (ii) mapping CES arising from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 55 publications
(81 reference statements)
0
19
0
1
Order By: Relevance
“…Combining trade-off analysis with stakeholder engagement offers potential to facilitate effective knowledge exchange between decision-makers, while also capitalising on important expertise and understanding that would be otherwise missed from trade-off analysis alone (Galafassi et al 2017), as well as highlighting stakeholder typology differences in ecosystem service perception (Darvill & Lindo 2016). Including questionnaires as part of ecosystem service analysis, for instance, can help to capture the complexity of socio-ecological systems by incorporating stakeholder values and identifying drivers of change (Andersson et al 2015; spatial distribution of social benefits, especially for cultural services, which are difficult to estimate (Canedoli et al 2017;Reilly et al 2018). The use of participatory approaches are therefore vital for including the social demand of ecosystem service trade-offs, which is often neglected, and hence may avoid potential conflict of natural resource use and management (García-Nieto et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Combining trade-off analysis with stakeholder engagement offers potential to facilitate effective knowledge exchange between decision-makers, while also capitalising on important expertise and understanding that would be otherwise missed from trade-off analysis alone (Galafassi et al 2017), as well as highlighting stakeholder typology differences in ecosystem service perception (Darvill & Lindo 2016). Including questionnaires as part of ecosystem service analysis, for instance, can help to capture the complexity of socio-ecological systems by incorporating stakeholder values and identifying drivers of change (Andersson et al 2015; spatial distribution of social benefits, especially for cultural services, which are difficult to estimate (Canedoli et al 2017;Reilly et al 2018). The use of participatory approaches are therefore vital for including the social demand of ecosystem service trade-offs, which is often neglected, and hence may avoid potential conflict of natural resource use and management (García-Nieto et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In a Web of Science search (12 March 2018; Figure 1), we found that publications reporting participatory research have increased over time, but very few of those research efforts involve geospatial approaches, and most of those do not involve geospatial modeling. Maps are often used in participatory research to identify locations of ecosystem services or perceived value (e.g., [8][9][10][11]). Maps can also be boundary objects [12,13] that mediate discussions about problematic issues.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, only fine-grain assessment at the site-level can shed information on the differences in recreational demand for protected areas among different social groups (e.g., local day-trippers, domestic tourists, and international tourists) [26][27][28] and equity issues among the beneficiaries of different social-demographic characteristics (e.g., education level, income, gender, and age.) in terms of a site's accessibility [29,30].…”
Section: Introductionmentioning
confidence: 99%